Extension to HiRLoc Algorithm for Localization Error Computation in Wireless Sensor Networks - Swati Saxena (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
Wireless sensor networks (WSNs) have gained importance in recent years as this support a large spectrum of applications such as automotive, health, military, environmental, home and office. Various algorithms have been proposed for making this technology more adaptive the existing algorithms address issues such as safety, security, power consumption, lifetime and localization. This paper presents an extension to HiRLoc algorithm and highlights its benefits. Extended HiRLoc significantly reduce the average localization error by suggesting a new method directional antenna based scheme.